A Novel AIE Fluorescent Probe for Cu2+ Recognition Based on Salicylaldehyde‐azine System. Issue 45 (1st December 2022) - Liu, Jie; Leng, Chengrang; Chen, Quanan; Liang, Qirui; Li, Chenhao; Li, Shuo; Zhang, Zhen; Xiao, Lufei
Abstract: A novel compound, obtained by one‐step condensation of salicylaldehyde and hydrazine hydrate, has been synthesized, and characterized by various spectroscopic techniques. The crystal structure and photophysical properties of the compound have been analyzed in detail. The compound exhibits distinct aggregation‐induced emission in acetonitrile‐water, and high selectivity towards Cu 2+ ions, fast response time, and low detection limit (5.7×10 −7 mol/L). In this sense, the compound can be applied as a potential probe for detecting copper (II) ions. Abstract : A novel compound was obtained by one‐step condensation of salicylaldehyde and hydrazine hydrate and characterized by NMR, FT‐IR, X‐Ray diffraction analysis and et al, which exhibits distinct aggregation‐induced emission in acetonitrile‐water and high selectivity towards Cu2+ ions, fast response time, and low detection limit (5.7×10 −7 mol/L).